Logistic Regression With Non-Financial Liability Ratings on The Indonesia Stock Exchange - Muklis Kanto; Annas Lalo (Journal Research of Social Science, Economics, and Management, 2023)
Companies that issue bonds have an obligation to pay interest regularly according to a predetermined period of time and the principal at maturity. This study aims to determine and analyze the effect of profitability on bond ratings in non-financial companies listed on the IDX for the 2018-2021 period. The analytical method used in this study is a quantitative analysis method using Microsoft Excel 2016 software and SPSS (Statistical Package for Social Sciences) version 26.0 as tools to test data. The purpose of this analysis is to get the relevant information contained in the data and use the results to solve a problem. The results of this study state that a positive liquidity value indicates that companies with high liquidity are most likely to be in efficient conditions, for example, companies do not use financing through bonds because companies have large internal funds and tend to choose to use internal funds first compared to external financing sources such as issuance of bonds resulting in high corporate value and affect the bond rating. These results indicate that liquidity has a positive influence on bond ratings of non-financial companies listed on the Indonesia Stock Exchange in 2018-2021, thus supporting the research hypothesis. This is because liquidity shows a positive direction, where the higher the level of liquidity, the greater the acquisition of a non-financial company's bond rating.